2011
DOI: 10.1177/089875641102800204
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Human Periodontal Pathogens in Oral Swab Specimens from Dogs in Japan

Abstract: Periodontal diseases are known to be major diseases in humans, and are also common in dogs. The purpose of the present study was to analyze the distribution of periodontitis-related bacterial species using oral swab specimens collected from 26 pet dogs. The distribution of an animal gingival organism Porphyromonas gulae, in addition to 10 human periodontitis-related bacterial species, including Porphyromonas gingivalis, Treponema denticola, Tannerella forsythia, Capnocytophaga ochracea, Capnocytophaga sputigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 28 publications
1
66
0
Order By: Relevance
“…The diseases are composed of gingivitis, a reversible condition that features limited inflammation of gingival tissue, and periodontitis, which indicates destruction of periodontal tissues, such as the cementum, periodontal ligaments and supportive bone [8]. It has been summarized that the distribution frequency of gingivitis in dogs aged from 0 to 14 years old (average; approximately 6 years old) ranges from 95-100%, while that of periodontitis is from 50-70% [3].Our previous study analyzed the distribution of 10 human periodontitis-related species in dogs and found that specific species, such as Tannerella forsythia and Campylobacter rectus, were frequently detected [5]. In addition, Porphyromonas gulae, a major pathogen of periodontitis in dogs [2], was also detected at a high frequency [5].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The diseases are composed of gingivitis, a reversible condition that features limited inflammation of gingival tissue, and periodontitis, which indicates destruction of periodontal tissues, such as the cementum, periodontal ligaments and supportive bone [8]. It has been summarized that the distribution frequency of gingivitis in dogs aged from 0 to 14 years old (average; approximately 6 years old) ranges from 95-100%, while that of periodontitis is from 50-70% [3].Our previous study analyzed the distribution of 10 human periodontitis-related species in dogs and found that specific species, such as Tannerella forsythia and Campylobacter rectus, were frequently detected [5]. In addition, Porphyromonas gulae, a major pathogen of periodontitis in dogs [2], was also detected at a high frequency [5].…”
mentioning
confidence: 99%
“…Our previous study analyzed the distribution of 10 human periodontitis-related species in dogs and found that specific species, such as Tannerella forsythia and Campylobacter rectus, were frequently detected [5]. In addition, Porphyromonas gulae, a major pathogen of periodontitis in dogs [2], was also detected at a high frequency [5].…”
mentioning
confidence: 99%
See 3 more Smart Citations